2004
DOI: 10.1002/cncr.20278
|View full text |Cite
|
Sign up to set email alerts
|

Diversity matters: Unique populations of women and breast cancer screening

Abstract: BACKGROUND. Ethnic differences in breast cancer screening behaviors are well established. However, there is a lack of understanding regarding exactly what causes these differences and which characteristics in low-screening populations should be targeted in an effort to modify screening behavior. METHODS.Stratified cluster sampling was used to recruit 1364 women (ages 50 -70 years) from 6 ethnic groups: African-American women; U.S.-born white women;English-speaking Caribbean, Haitian, and Dominican women; and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 59 publications
5
71
1
Order By: Relevance
“…5 Second, the effect sizes for the psychological variables are small, although their magnitude was on par with those of known predictors of screening, including age and income. Perhaps more importantly, whereas age and income are immutable for intervention purposes and are better suited to identifying ''at-risk'' populations, psychological characteristics may be particularly amenable to change (47); modest effects may be of considerable practical significance (37). It seems likely, for example, that a modicum of dispositional anxiety is useful in promoting more active screening profiles, although how such anxiety might best be activated remains unclear at this point.…”
Section: Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Second, the effect sizes for the psychological variables are small, although their magnitude was on par with those of known predictors of screening, including age and income. Perhaps more importantly, whereas age and income are immutable for intervention purposes and are better suited to identifying ''at-risk'' populations, psychological characteristics may be particularly amenable to change (47); modest effects may be of considerable practical significance (37). It seems likely, for example, that a modicum of dispositional anxiety is useful in promoting more active screening profiles, although how such anxiety might best be activated remains unclear at this point.…”
Section: Independent Variablesmentioning
confidence: 99%
“…Missing from this developing picture thus far, however, is a systematic examination of the emotion and emotion regulatory variables that breast cancer screening research has suggested may be critical to understanding screening in diverse populations (47,48). One study examined prostate cancer worry in relation to prostate screening, although it focused on differences between symptomatic and asymptomatic men (49).…”
mentioning
confidence: 99%
“…Data on cancer incidence, mortality, and health disparities among immigrants in the U.S. remain limited [4][5][6][7]. Immigrant minorities continue to experience disproportionately higher cancer incidence and mortality rates for many cancers [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Consedine et al found that Haitian men reported significantly lower prostate cancer screening compared with U.S. born whites [3]. Haitian women have been found to be less likely to utilize breast cancer screening [4,5], and have lower Papanicolaou (Pap) test screening rates than native-born Black and Latina peers [6], and a higher incidence of invasive cervical cancer than U.S.-born black women [7]. Regardless of ethnicity or socioeconomic status, increasing cancer screening results in early detection of many cancer types, lowers incidence of late stage cancer diagnosis, and improves cancer outcomes, considerably enhancing survival rates [8].…”
Section: Introductionmentioning
confidence: 99%